2016
DOI: 10.1053/j.gastro.2016.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Reduces Endoscopic, but Not Clinical, Recurrence of Crohn’s Disease After Ileocolonic Resection

Abstract: Infliximab is not superior to placebo in preventing clinical recurrence after CD-related resection. However, infliximab does reduce endoscopic recurrence. ClinicalTrials.gov ID NCT01190839.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
161
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(176 citation statements)
references
References 52 publications
7
161
3
5
Order By: Relevance
“…In 3 small randomized controlled trials, anti-TNFs compared with placebo or mesalazine were highly effective in preventing endoscopic recurrence in CD patients at high and low risk of recurrence [18,21]. This finding was recently confirmed by the results of the PREVENT study, in which the rates of endoscopic recurrence, prior to or at week 76, were 30.6 and 60% in the infliximab and placebo groups, respectively ( p < 0.001) [22]. …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In 3 small randomized controlled trials, anti-TNFs compared with placebo or mesalazine were highly effective in preventing endoscopic recurrence in CD patients at high and low risk of recurrence [18,21]. This finding was recently confirmed by the results of the PREVENT study, in which the rates of endoscopic recurrence, prior to or at week 76, were 30.6 and 60% in the infliximab and placebo groups, respectively ( p < 0.001) [22]. …”
Section: Discussionmentioning
confidence: 93%
“…Recently, infliximab has been shown to be more effective than placebo in preventing endoscopic but not clinical recurrence [22]. The POCER study showed that a strategy based on endoscopic lesions rather than clinical symptoms is effective for the prevention and treatment of post-operative recurrence, at least in high-risk patients [23].…”
Section: Introductionmentioning
confidence: 99%
“…The PREVENT trial showed an efficacy of infliximab vs placebo in preventing endoscopic POR at 18 months, although this was not the case for its primary outcome, namely clinical POR. 7 The effect of infliximab was lower than expected, according to the pilot study by Regueiro et al, 3 which could be explained by differences in study populations. The first study concerned 24 high-risk patients, whereas in PREVENT a wider group of less risky patients was included.…”
mentioning
confidence: 86%
“…Furthermore, in APPRECIA, the estimated drop-out rate of 10% was clearly underestimated [26% in PREVENT; 15% in POCER]. 7,8 Second, Lopez-Sanroman et al chose to include all operated patients, without taking into account risk factors for POR like active smoking, previous resection, or penetrating disease. Although these risk factors have not been validated in a prospective setting, retrospective studies repeatedly showed their implication in POR.…”
mentioning
confidence: 99%
See 1 more Smart Citation